PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY - TWO STRAY TERHADAP HASIL BELAJAR IPS (STUDI EKSPERIMEN KUASI SISWA KELAS IVD SD NEGERI 184 PEKANBARU) - Putri, Amelia; Antosa, Zariul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This experimental study aims to determine the effect of the application of cooperative learning model Two Stay - Two Stray on learning outcomes IPS IVD grade students of SD Negeri 184 Pekanbaru). The research design was pretest-posttest control group design. In this design the experimental group and the control is not selected at random. In this study, IVC class is a class of 36 students control the number of people who apply conventional learning models. And the experimental class is class IVD by the number of students 36 people who apply the cooperative model types -Two Stay Two Stray. At an average of experimental classes increased from an average of 59 to 70 pretest result average yield postes.Untuk determine whether there is a significant difference between the experimental class and control class t test was used based on the pretest t test obtained t = -7.697 <ttabel = 2,000 then both classes there is no significant difference postes t test while the results obtained t = 2.15 <table = 2.000 then there are significant differences between the two classes. From the research the influence of cooperative learning model Two Stay - Two Stray to the learning outcomes of students in the experimental class IPS is equal to 55%. while 45% are influenced by other factors.Key Words: Cooperative type two stay - two stray model based on environment, social science learning outcomes